2010
DOI: 10.1002/ajmg.a.33385
|View full text |Cite
|
Sign up to set email alerts
|

Genetic health professionals and the communication of genetic information in families: Practice during and after a genetic consultation

Abstract: The communication of genetic information in families is an important process which can inform family members that they are at risk. However, evidence suggests that at-risk family members are often uninformed. Genetic health professionals have a role to assist consultands to communicate genetic information to their family members. Therefore, the aim of this study was to investigate genetic health professionals' practice with regard to the familial implications of a genetic diagnosis and subsequent family commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 17 publications
1
44
0
Order By: Relevance
“…33,34 Assisting consultands in the communication of information to at-risk relatives. This theme comprises nine papers with studies focussing on professionals' practice [35][36][37] and specific interventions to assist consultands in the communication of information to at-risk relatives. [38][39][40][41][42][43] Features of practice included psychoeducational guidance and information aids that were used as adjuncts to clinical practice.…”
Section: Studies Included In Quantitative Synthesismentioning
confidence: 99%
“…33,34 Assisting consultands in the communication of information to at-risk relatives. This theme comprises nine papers with studies focussing on professionals' practice [35][36][37] and specific interventions to assist consultands in the communication of information to at-risk relatives. [38][39][40][41][42][43] Features of practice included psychoeducational guidance and information aids that were used as adjuncts to clinical practice.…”
Section: Studies Included In Quantitative Synthesismentioning
confidence: 99%
“…The mean number of information statements communicated to patients was 21 (range [16][17][18][19][20][21][22][23][24][25][26].…”
Section: Participantsmentioning
confidence: 99%
“…18 A worldwide survey of genetic counselling practice in facilitating family communication found that, although 90% of participants stated that they always identify at-risk relatives and encourage family communication, 41% never write a letter specifically for at-risk relatives. 19 This observational study aimed to (i) compare the accuracy of information among patients and relatives following genetic counselling with index patients about a BRCA1/2 mutation, (ii) compare the accuracy of information about general genetics and hereditary cancer and (iii) examine whether accuracy among relatives improved when information was provided directly by genetics health professionals. This was part of a larger study examining the experience and process of family communication using qualitative and quantitative methods.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in contrast with an international survey of genetic health professionals' practice that found that counseling consultands about at-risk family members and family communication occurred consistently during consultations. 19 However, a lack of documentation in the genetics files does not mean that this discussion did not occur; it may have occurred and not been recorded. This may have significant ramifications if there is litigation by at-risk family members who are unaware of their genetic risk.…”
Section: 13mentioning
confidence: 99%